2011
DOI: 10.1177/1090198110394174
|View full text |Cite
|
Sign up to set email alerts
|

A Family and Community Focused Lifestyle Program Prevents Weight Regain in Pacific Islanders

Abstract: Preventing weight regain after the loss of excess weight is challenging for people, especially for ethnic minorities in the U.S. A 6-month weight loss maintenance intervention designed for Pacific Islanders, called the PILI Lifestyle Program (PLP), was compared with a 6-month standard behavioral weight loss maintenance program (SBP) in a pilot randomized controlled trial using a community-based participatory research (CBPR) approach. Adult Pacific Islanders (n=144) were randomly assigned to either PLP (n=72) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 30 publications
(45 reference statements)
0
65
0
Order By: Relevance
“…In real-world settings, it is recommended for weight-management programmes to have rolling retention policies and procedures, to enable participants to be captured in the programme and to allow flexibility in their entry and exit. Like other behavioural change programmes in the health arena, for example in smoking (48) or alcohol management (49) , weight management also involves periods of relapse and re-commitment (50)(51)(52) that can be difficult to capture in limited-time research interventions. Our study enabled us to explore, with the participants, how they felt they could manage their programme participation in the face of trying to manage life crises and changes.…”
Section: Discussionmentioning
confidence: 99%
“…In real-world settings, it is recommended for weight-management programmes to have rolling retention policies and procedures, to enable participants to be captured in the programme and to allow flexibility in their entry and exit. Like other behavioural change programmes in the health arena, for example in smoking (48) or alcohol management (49) , weight management also involves periods of relapse and re-commitment (50)(51)(52) that can be difficult to capture in limited-time research interventions. Our study enabled us to explore, with the participants, how they felt they could manage their programme participation in the face of trying to manage life crises and changes.…”
Section: Discussionmentioning
confidence: 99%
“…Data for this study comes from 100 Pacific Islander adults (18 years of age and older) who completed one of two POP 9‐month weight loss maintenance interventions (11). As part of the POP lifestyle interventions, all 100 participants completed a 3‐month weight loss program (WLP) to initiate weight loss and were then randomized into either a 6‐month family and community focused weight loss maintenance program, called the PILI Lifestyle Program (PLP; n = 49), or a standard behavioral weight loss maintenance program (SBP; n = 51).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Using a CBPR approach, the POP community‐academic partnership conducted a pilot RCT to compare the effectiveness of two 9‐month lifestyle interventions for NHs/PIs who were given a modest goal of losing ≥3% of their baseline body weight. A description of the POP and the results from the RCT has been previously published (10–12). We report here our examination of the sociodemographic, behavioral, and biological factors related to success at achieving ≥3% weight loss in overweight and obese Native Hawaiians, Chuukese, and other Pacific Islanders who completed the 9‐month POP lifestyle interventions.…”
Section: Introductionmentioning
confidence: 99%
“…For additional details on the PLP, see Mau and colleagues (2010) and Kaholokula and colleagues (2012). 15-16 The PLP was found to be effective in a randomized controlled trial and the POP's focus turned to dissemination. 15-16 However, a dissemination model or framework was needed to guide these efforts.…”
Section: The Pili 'Ohana Projectmentioning
confidence: 99%
“…34 Furthermore, the intervention was tested through a randomized control trial and found to be effective with NH/PP. 16 …”
Section: Elements Of the Ccm Modelmentioning
confidence: 99%